(3ebGdI aj GdaUOs - (3CHhHcQ GdQGRj , eMeO Hf RcQjG, CHh HcQ GdQGRj,J (B311 (3g` s
(3ChdgG (B:s
(3ebGdI GfTGgG eMeO Hf RcQjG GdQGRi ai GdaUO bGd GdbjaGd jfHZi Gf jfRd Yf GdYVdI fMh GddMe s
(3BNQgG (B:s
(3hCeG Gf jMd eG bO LeO ai ae GdbQHI ef GdOe HTYQI aGf Pdc GUdM ef dHg hSWMg JeJ GdQSGdI s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(1538) s
Keywords: (3GdWHs